On certain subclasses of multivalent functions associated with an extended fractional differintegral operator - Patel, J.; Mishra, A.K. (Journal of mathematical analysis and applications, 2007)
In the present paper an extended fractional differintegral operator Ω z ( λ , p ) ( − ∞ < λ < p + 1 ; p ∈ N ) , suitable for the study of multivalent functions is introduced. Various mapping properties and inclusion relationships between certain subclasses of multivalent functions are investigated by applying the techniques of differential subordination. Relevant connections of the definitions and results presented in this paper with those obtained in several earlier works on the subject are also pointed out.